2014
DOI: 10.1007/s00265-014-1760-5
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of flow condition and parasitism on shoaling behaviour of female guppies Poecilia reticulata

Abstract: Group living in fish can provide benefits of protection from predators and some parasites, more efficient foraging for food, increased mating opportunities and enhanced energetic benefit when swimming. For riverine species, shoaling behaviour can be influenced by various environmental stressors, yet little is known how flow rate might influence the shoaling of diseased fish shoals. In view of the increasingly unpredictable flow rates in streams and rivers, this study aimed to assess the combined effect of flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…Of particular relevance to our study, Gyrodactylus infection influences, and is influenced by, various aspects of behaviour. For instance, Gyrodactylus ‐infected guppies show impaired swimming ability and reduced activity due to fin damages (López, ; Cable et al ., ), reduced shoaling cohesion (Croft et al ., ; Hockley et al ., ) and lower boldness (Richards, ). In addition, infection risk is influenced by shoaling and other behaviours (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Of particular relevance to our study, Gyrodactylus infection influences, and is influenced by, various aspects of behaviour. For instance, Gyrodactylus ‐infected guppies show impaired swimming ability and reduced activity due to fin damages (López, ; Cable et al ., ), reduced shoaling cohesion (Croft et al ., ; Hockley et al ., ) and lower boldness (Richards, ). In addition, infection risk is influenced by shoaling and other behaviours (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Although we expected the two high predation treatments (HP-HF and HP-LF) to have greater shoal compactness than the LP-LF group, we found no significant difference in shoal cohesion. Increased shoal size increases competition for other social factors such as mating (Alexander 1974;Hoogland and Sherman 1976) and also increases the risk of parasitism (Phillips 1924;Freeland 1976;Duffy 1983), which could lead to reduced shoal cohesiveness (Alexander 1974;Mikheev 2009;Hockley et al 2014). Thus, the tendency of fish to stay close to each other due to predation pressure may not be strong enough to overcome the tendency to repel each other within the shoal in order to reduce competition for other social factors (Mikheev 2009;Shelton et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, shoaling tendencies have been observed to diminish in higher flow rates in common minnow (Garner, 1997), three-spined sticklebacks (Sneddon et al, 2006), and zebrafish (Suriyampola et al, 2017). Contrastingly, Hockley et al (2014) showed that in no-flow conditions, the shoaling tendencies of Trinidadian guppies (Poecilia reticulate Peters, 1859) were significantly reduced compared to those experiencing flowing water, but only following the introduction of Gyrodactylus turnbulli Harris, 1986 infection. This indicated that parasitism may have a greater influence than flow in determining shoaling preferences.…”
Section: Introductionmentioning
confidence: 96%